Review of 23 patients affected by the stiff man syndrome: clinical subdivision into stiff trunk (man) syndrome, stiff limb syndrome, and progressive encephalomyelitis with rigidity. Issue 5 (1st November 1998) - Barker, R A; Revesz, T; Thom, M; Marsden, C D; Brown, P
Abstract : OBJECTIVE: To investigate whether the stiff limb syndrome may be separated from the stiff man syndrome and progressive encephalomyelitis with rigidity on simple clinical grounds, and whether such a distinction has implications for aetiology, treatment, and prognosis. METHODS: Twenty three patients referred over a 10 year period with rigidity and spasms in association with continuous motor unit activity, but without evidence of neuromyotonia, extrapyramidal or pyramidal dysfunction or focal lesions of the spinal cord were reviewed. The patients were divided into those with an acute or subacute illness, leading to death within 1 year, and those with a chronic course. The latter were divided into those in whom rigidity and spasms dominated in the axial muscles, or in one or more distal limbs, at the time of their first assessment. RESULTS: This simple division identified three distinct groups of patients. (1) Progressive encephalomyelitis with rigidity: two patients had a rapidly progressive condition characterised by widespread rigidity which resulted in death within 6 and 16 weeks. One patient had negative anti-GAD and anti-neuronal antibodies, but had markedly abnormal CSF and widespread denervation. The principal pathological findings in this case were a subacute encephalomyelitis which primarily affected the grey matter. In the remaining patient anti-GAD antibodies were not tested, and postmortem was refused. (2) Stiff man syndrome: eight patients had rigidity and painful spasms of the lumbar paraspinal, abdominal, and occasionally proximal leg muscles associated with a lumbar hyperlordosis. There was no involvement of the upper limbs, distal lower limbs, sphincters or cranial nerves. Seven had anti-GAD antibodies and most had additional evidence of autoimmune disease. Neurophysiologically there was continuous motor unit activity with abnormal exteroceptive reflexes, but a normal interference pattern during spasms. The patients all responded to baclofen/diazepam and remained ambulant. (3) Stiff limb syndrome: thirteen patients had rigidity, painful spasm, and abnormal postures of the distal limb, usually the leg. About half went on to develop sphincter or brainstem involvement. Generalised myoclonic jerks were not a feature. Only two had truncal rigidity, and another two had anti-GAD antibodies. Most had no evidence of autoimmune disease. Neurophysiologically they had continuous motor unit activity in the affected limb, abnormal exteroceptive reflexes, and abnormally segmented EMG activity during spasms. The disease ran a protracted course, and most patients had only a partial response to baclofen or diazepam. About half became wheelchair bound. CONCLUSIONS: The stiff limb syndrome seems distinct from the stiff man syndrome or progressive encephalomyelitis with rigidity, and is an important cause of rigidity and spasm in the setting of continuous motor unit activity.